The Effects of Multiple Chronic Conditions on Adult Patient Readmissions and Hospital Finances: A Management Case Study - Michael Mihailoff MBA, RRT; Shreyasi Deb PhD, MBA; James A. Lee MS; Joanne Lynn MD, MA, MS (SAGE Publishing, 2017)
Medicare and other payers have launched initiatives to reduce hospital utilization, especially targeting readmissions within 30 days of discharge. Hospital managers have traditionally contended that hospitals would prosper better by ignoring the penalties for high readmission rates and keeping the beds more full. We aimed to test the financial effects of admissions and readmissions by persons with and without specified chronic conditions in one regional hospital. This is a management case study with a descriptive brief report. This study was conducted at Winchester Memorial Hospital, a general hospital in a largely rural area of Virginia, 2010-2015. The total margin per admission varied by diagnosis, with the average patient diagnosed with chronic obstructive pulmonary disease, heart failure, pneumonia, or chronic renal disease having negative margins. The largest per-patient losses were in diagnostic categories coinciding with the highest readmission rates. The margin declined into substantial losses with an increasing number of chronic conditions, which also corresponded with higher readmission rates. Patients with 5 or more clinical conditions had highest risk of readmission within 30 days (24.8%) and had an average total loss of $865 per admission in 2015. The adverse financial effects worsened between 2010 and 2015. This hospital might improve its finances by investing in strategies to reduce chronic illness hospitalizations, especially those with multiple chronic conditions and high risk of readmission. These findings counter the common claim that the hospital would do better to fill beds rather than to work on efficient utilization. Other hospitals could replicate these analyses to understand their situations.